Efectividad del uso de heparina de bajo peso molecular en la profilaxis de trombosis venosa profunda en cirugías ortopédicas, realizadas en el Hospital Manuel Ygnacio Monteros Valdivieso de la ciudad de Loja en el periodo enero-diciembre del año 2013 - Campoverde Salas, Karina del Cisne (2015)
The low molecular weight heparins (LMWH) have been studied in the prevention and treatment of thromboembolic disease due to its potential advantages compared with other anticoagulants: predictability, dose, response, ease of management and lessening in laboratory requirements. The present research work was carried out in Manuel Ygnacio Monteros Valdivieso Hospital of Loja city, period January – July 2014. This work had the aim of determining the effectiveness of using low molecular weight heparins (LMWH) in the immediate postoperative such as deep venous thrombosis prophylaxis in major orthopedic surgeries performed in the place of study; as well as checking for signs and clinical symptoms of this disease according to Wells scale, to determine the probability of submission of this pathology; it was a retrospective, descriptive, analytical, cross-sectional study. It was taken into account patients who have been subjected to major orthopedic surgeries, such as long bones osteosynthesis, hip and knee joints replacements, who have received thromboprophylaxis with low molecular weight heparins and have been operated in the period from January to December 2013. It was determined the effectiveness of thromboprophylaxis performed in the study area taking into account the low incidence of symptoms and signs presented by the patiets, after administration of low molecular weight heparin, furthermore it is noted that after hospital discharge there were prescribed orally heparins for a given time, and no patient had a thrombotic event. The model of Wells, ranked 127 patients into a moderate probability of developing deep vein thrombosis, and 26 within a high probability. Keywords: deep vein thrombosis, low molecular weight heparin, model of Wells.